Detection of host and pathogen biomarkers for Mycobacterium bovis infection in African big cats (lions (Panthera leo), leopards (Panthera pardus), cheetahs (Acinonyx jubatus)) - Gumbo, Rachiel (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.